2013
DOI: 10.1053/j.gastro.2013.01.049
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Gluten-Free Diet in Patients With Irritable Bowel Syndrome-Diarrhea: Effects on Bowel Frequency and Intestinal Function

Abstract: Background & Aims Patients with diarrhea-predominant irritable bowel syndrome (IBS-D) could benefit from a gluten-free diet (GFD). Methods We performed a randomized controlled 4-week trial of a gluten-containing diet (GCD) or GFD in 45 patients with IBS-D; genotype analysis was performed for HLA-DQ2 and HLA-DQ8. Twenty-two patients were placed on the GCD (11 HLA-DQ2/8–negative and 11 HLA-DQ2/8–positive) and 23 on the GFD (12 HLA-DQ2/8−negative and 11 HLA-DQ2/8–positive. We measured bowel function daily, smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
335
5
30

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(381 citation statements)
references
References 27 publications
11
335
5
30
Order By: Relevance
“…However, global symptoms and abdominal pain worsened from the end of the run-in phase to day 7 of treatment [45]. Conversely, a single-center, controlled study of 45 patients with IBS-D showed that patients randomly assigned to a gluten-free diet had a significant decrease in daily stool frequency from baseline compared with a diet containing gluten after 4 weeks (P = 0.04) [42]. These results raise the possibility that the positive effect of a gluten-free diet in patients with IBS may be a nonspecific consequence of reducing the intake of FODMAPs, given that wheat is one of the possible sources of FODMAPs.…”
Section: Gluten-free Dietsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, global symptoms and abdominal pain worsened from the end of the run-in phase to day 7 of treatment [45]. Conversely, a single-center, controlled study of 45 patients with IBS-D showed that patients randomly assigned to a gluten-free diet had a significant decrease in daily stool frequency from baseline compared with a diet containing gluten after 4 weeks (P = 0.04) [42]. These results raise the possibility that the positive effect of a gluten-free diet in patients with IBS may be a nonspecific consequence of reducing the intake of FODMAPs, given that wheat is one of the possible sources of FODMAPs.…”
Section: Gluten-free Dietsmentioning
confidence: 98%
“…However, before entertaining a diagnosis of nonceliac wheat sensitivity, patients should be properly evaluated with celiac serological screening and an upper endoscopy with biopsies to rule out celiac sprue. Because studies have shown that a gluten-free diet can improve IBS symptoms, at least in some patients, nonceliac wheat sensitivity may comprise a subset of patients with IBS [40,42]. A gluten-free diet was also shown to improve IBS-related QOL from baseline in some patients with IBS [43].…”
Section: Gluten-free Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large Italian retrospective study on 920 adult patients with irritable bowel syndrome (IBS) demonstrated that 30 % were positive to a wheat double-blind placebo-controlled food challenge (DBPCFC) and therefore classified as NCGS (74 % suffering from multiple food sensitivities) [10 • ]. Finally, a recent study on patients with diarrhea predominant IBS suggested that gluten withdrawal improved stool frequency, while its administration negatively influenced intestinal permeability [11].…”
mentioning
confidence: 99%
“…Studies suggest that the prevalence of CD is increased in individuals with IBS; however, evidence is conflicting, and current guidelines do not always recommend screening for CD in these individuals. Prevalence of biopsy-proved CD in cases meeting diagnostic criteria for IBS was more than 4-fold that in controls without IBS [3].With data showing that patients with IBS-D may benefit from gluten free diet (GFD), GFD is used with increasing frequency in IBS-D patients [4][5][6]. Although there is little harm beyond cost to a patient on a balanced GFD,CD may be overlooked and complications ignored.…”
mentioning
confidence: 99%